Comparison of Dimensional Accuracy of Cast Obtained from Polyvinyl Siloxane Impression with Different Putty-Wash Techniques and Spacer Thickness - In Vitro Study - Pandey, Anisha; Mathema, S.R.B.; Maharjan, S.K. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: Dimensional accuracy of cast obtained after making impressions is crucial factor for the quality of fixed prosthodontic treatment. The impression technique with different thickness of putty wash material is critical factor affecting this accuracy. There is much discussion in the dental literature concerning the effect of this impression technique on the accuracy of cast restorations.Materials and methods: This in-vitro study was carried out in 60 impression made from master model with Polyvinyl siloxane impressions material using single step putty- wash technique and two step putty-wash technique with varying spacer thickness (0.5mm, 1mm, 1.5 mm). It was further divided into four groups. Group I: Single step putty-wash impression technique, Group II: Two step putty-wash impression technique with 0.5mm spacer, Group III: Two step putty-wash impression technique with 1mm spacer, Group IV: Two step putty-wash impression technique with 1.5mm spacer. Each group consists of 15 impressions. Casts were poured using type IV dental stone after 1 hour. After 24 hour the die of each cast was scanned using CAD/CAM digital scanner and measured mesiodistally, facio-lingually, height (cervico-occlusally), interabutment or interdie distances. The data were recorded and statically analyzed.Results: The highest mean values of mesio-distal, bucco-lingual, cervico-occlusal distances were shown by Group I, whereas the inter-die distance showed equal mean value in Group I, II and III. With the increase in the spacer thickness, the mean value also increases in mesio-distal distance. The mean measurement of bucco-lingual dimension was highest when spacer thickness was 0.5mm and it declined with the increase in spacer thickness. The spacer thickness had no effect on cervico-occlusal and inter-die dimensions.Conclusions: Within the limitations of the study, accuracy of cast obtained from single step putty-wash technique was more accurate than two step putty-wash technique. In two step putty-wash technique, 1.5 mm thickness of spacer showed more accurate cast in comparison to 0.5mm and 1mm.